An Overprotective Nose? Implicit Bias Is Positively Related to Individual Differences in Body Odor Disgust Sensitivity - Zakrzewska, Marta Zuzanna; Liuzza, Marco Tullio; Lindholm, Torun; Blomkvist, Anna; Larsson, Maria; Olofsson, Jonas K. (Frontiers in Psychology, 2020)
Body odors are universal elicitors of disgust, a core emotion that plays a key role in the behavioral immune system (BIS) -a set of psychological functions working to avoid disease. Recent studies showed that body odor disgust sensitivity (BODS) is associated with explicit xenophobia and authoritarianism. In the current experimental pre-registered study (https://osf.io/6jkp2/), we investigated the association between olfactory pathogen cues, BODS and implicit bias toward an outgroup (tested by an implicit association test, IAT). Results show that BODS is positively related to implicit bias towards an outgroup, suggesting that social attitudes may be linked to basic chemosensory processes. These attitudes were not influenced by background odors. Additionally, BODS was related to social, but not economic conservatism. This study extends the BIS framework to an experimental context by focusing on the role of disgust and body odors in shaping implicit bias.